Contesting Authority in Urban Islam: Mosque-Based Muslim Intellectuals and the Production of Religious Knowledge in Yogyakarta - Faiz, Abd Aziz; Noorhaidi, Noorhaidi (An-Nida', 2026)
Academic discourse on Muslim intellectual authority shows a pessimistic tendency alongside the development of new media and the post-Reformasi 1998. Muslim intellectuals are often positioned as actors who possess scholarly capacity, yet lack authority in the production of Islamic knowledge in the public sphere. This study challenges this assumption through an examination of the appropriation of Muslim intellectual authority in producing Islamic knowledge through the mosque and its online media. A qualitative method is employed. Primary data derive from observations of Muslim intellectual activities at Jenderal Sudirman Mosque Yogyakarta and public responses on the mosque’s online platforms. Additional data derive from interviews with mosque administrators and its audience. The study produces three findings. First, Muslim intellectuals build their scholarly authority in modern universities, while their public authority is consolidated through the mosque and its media. Second, they produce public Islamic discourse through critical approaches relevant to the challenges of urbanity and gain urban public support. Third, the mosque mediates the relationship between intellectual authority, the production of critical Islamic knowledge, and public religious commitment. These findings contribute to understanding the appropriation of Muslim intellectual authority in the production of Islamic knowledge through the everyday micro-practices of the mosque and its media in urban Yogyakarta.